Análise discursiva da Audiência Pública do Fórum Nacional de Educação no contexto da Consulta Pública do Ensino Médio realizada no ano de 2023 - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This dissertation investigates the discursive dynamics and tensions present in the public hearing of the National Education Forum (FNE), held within the context of the Public Consultation established by Ordinance No. 399/2024, aimed at evaluating and restructuring the National High School Policy. The study focuses on selected discursive formations (DF) that reflect different perspectives on the Reform. As the High School Reform, instituted by Law No. 13.415/2017, has sparked intense debate, this research seeks to understand how these discursive formations were expressed during the 2023 hearings. To this end, the dissertation adopts a discourse analysis approach grounded in the studies of Michel Foucault and his scholars, particularly drawing on the concepts of power-knowledge and regimes of truth, in order to identify the emerging discursive formations. The methodology includes the analysis of documents and video recordings from the public hearing, enabling a critical understanding of the discourses that influence educational reforms. This study highlights the importance of public hearings as spaces of negotiation and resistance, where power dynamics and ideological disputes over education in Brazil become evident. The research contributes to the understanding of discursive practices in educational policy and the impact of public consultation hearings on policy formulation in the country.
Discourse analysis of the Public Hearing of the National Education Forum in the context of the 2023 Public Consultation on Secondary Education
Keywords: Reforma do Ensino Médio; Políticas Educacionais; Análise do discurso; Michel Foucault; High School Reform; Educational Policies; Discourse Analysis; CIENCIAS HUMANAS::EDUCACAO; EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO